A retrospective study of ten-year data of patients treated in ege university medical school: sociodemographic characteristics of substance abusers - Doğanavşargil, G. Özge; Önen Sertöz, Özen; Coşkunol, Hakan; Şen, Gülseren (Journal of Dependence, 2004)
Objective: The aim of the study was to investigate the sociodemographic characteristics of substance abusers and characteristics of substance use of patients who were admitted to the Psychiatry Department of Ege University Medical School in the last decade.Method: We examined retrospectively, the patient reports, computer records of the patients who were admitted to Ege University Medical School in the last decade. All the data were collected and analyzed using descriptive analysis, chi-square and one-way ANOVA.Result: The sample of the study consisted of 325 patients who use substances and were treated in the last decade. The average age of the sample was 27.58 (sd=10.43) and beginning age to substance use was 18.80 (ss=8.20). Most of the patients were male (88.3%) and 11.7% of the patients were female. Multiple substances (30.8%) and cannabis (26.4%) were the most frequently used substances. The majority of the patients in study were young. Beginning age of inhalant use was significantly young. Unemployment rate was high (38%). Patients who use heroin had higher socioeconomical status and they had emigrated from a foreign country. A higher proportion of inhalant users lived in shantytowns as opposed to proper flats.Conclusion: According to Psychiatry Department of Ege University Medical School’s data, substance use is an important problem that effected young people. Epidemiologic studies are needed.
Keywords: Substance use; sociodemographic characteristics; clinical characteristics